2016
DOI: 10.1155/2016/5828959
|View full text |Cite
|
Sign up to set email alerts
|

Lower Level of Bacteroides in the Gut Microbiota Is Associated with Inflammatory Bowel Disease: A Meta-Analysis

Abstract: Background and Aims. Multiple studies have reported associations between inflammatory bowel disease (IBD) and the flora disequilibrium of Bacteroides. We performed a meta-analysis of the available data to provide a more precise estimate of the association between Bacteroides level in the gut and IBD. Methods. We searched PubMed/MEDLINE, EMBASE, Cochrane Library, Wiley Library, BIOSIS previews, Web of Science, CNKI, and ScienceDirect databases for published literature on IBD and gut microbiota from 1990 to 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
148
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(163 citation statements)
references
References 27 publications
11
148
2
2
Order By: Relevance
“…Results from mediaspecific growth suggested the overgrown colonies were mostly Shigella and E.coli and it was proven by metagenomic data of cecal samples at the genus level (Fg.2(e) and 2(f)). An increase in Proteobacteria is concomitant with increased inflammation [54]. It is important to note that the Firmicutes (F) from 60-70% and Bacteroidetes (B) from 30-35% on day zero turned to 10% (F) and 1% or less (B) for both BALB/c and C57BL/6 on day 5 or day 4, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results from mediaspecific growth suggested the overgrown colonies were mostly Shigella and E.coli and it was proven by metagenomic data of cecal samples at the genus level (Fg.2(e) and 2(f)). An increase in Proteobacteria is concomitant with increased inflammation [54]. It is important to note that the Firmicutes (F) from 60-70% and Bacteroidetes (B) from 30-35% on day zero turned to 10% (F) and 1% or less (B) for both BALB/c and C57BL/6 on day 5 or day 4, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The Bayesian approach is used to derive metabolite concentration in serum. The phase and baseline of raw spectrum were corrected and concentrations of metabolites were obtained through a profiler using Metaboanalyst [54][55][56][57].…”
Section: Metabolomic Analysis Of Nmr Datamentioning
confidence: 99%
“…Among toddlers at risk for the development of type 1 diabetes, an outgrowth of B Ovatus was associated with future development of associated antibodies . In patients with IBD, while most adult studies indicate that Bacteroides is depleted in this condition, studies in pediatric IBD patients have shown mixed results …”
Section: Microbiota Alterations In Jiamentioning
confidence: 99%
“…Dysbiosis including changes in abundance of Bacteroides is linked to an altered metabolite profile and illness. For example, lower levels of Bacteroides are associated with IBD [21]. The most prominent and best-characterized Bacteroides species are B. fragilis and B. thetaiotaomicron .…”
Section: Commensal Bacteria and Their Positive Influence On Healthmentioning
confidence: 99%